A política curricular dos multiletramentos para o ensino médio : disputas em torno da formação (1990 – 2019) - Lima, Laurina Tavares de Farias (2020)
From the 1990’s up to these days, the Brazilian educational policies have suffered influences of the neoliberalism, especially in the curriculum matter. Historically and especially in the past four decades, the high school level has gone through constant reforms and counter-reforms. Its curriculum approaches show the dualism of the general and the professional education. The innovations brought by the Information and Communication Digital Technologies (TDICs) led the curriculum to serve market-based policies, making multiliteracies central in the studies on language and writing social uses for high school students to develop cognitively and deal with the new ways of working. This study is part of the Education Graduate Program (PPGEdu) of the Federal University of Mato Grosso (UFMT), Rondonópolis campus. It focuses on the multiliteracies curriculum policies for the high school level and presents the following research questions: how do the socioeconomic demands influence the centrality of multiliteracies in the curriculum and affect the education process for students who depend on public education? What are the perceptions of the agents in/of this process? Considering these questions, the study aims to investigate and analyze the perceptions of the teachers on the political and educational implications of the centrality of multiliteracies in the curriculum for high school students. For that we established the following specific objectives: a) to analyze the centralization of multiliteracies in the high school curriculum policy taking into account the hegemonic senses of multiliteracy since the 1990’s, and b) to investigate and analyze the curriculum demands which promote the relations between the needs of the productive sector and the uncertain and precarious reality of multiliteracies in students’ education. The guiding approach of this study is based on bibliographic and documental research, plus field research in a public school of the state system, in the city of Primavera do Leste-MT. As our theoretical method, we used the Policy cycle approach and the Thematic oral history, in a qualitative approach. The results show: the implications of the approaches and of the high school reforms for meeting the (neo)liberal society demands, with the presence of educational dualism in the educational approaches, in a historic perspective; the relation between work and education, under the logic of the market; the curriculum policy which has been going through reforms and counter-reforms with the correspondence of the search for the instrumental rationality, effectiveness and efficiency. Given the meaning disputes, critical multiliteracies are excluded from the curriculum and substituted by the “know-how”, with skills and competences oriented to a positivist and conductivist knowledge. The perceptions of the teachers on this process were incipient, ambiguous and fragilized by a process of meaning negotiation which has oppressed their practice through assessment, responsibilization, precariousness, performativity, resulting in practices for the acceptance of the dominant project for students. However, we understand that the recontextualization of the policies has enabled the process of resistance and search for emancipation for teachers and students.